Evaluation of Etiopathogenesis, Clinical Profile and Lrinec Scoring in Necrotising Soft Tissue Infections (Indian Journal of Public Health Research & Development, 2020)
Necrotising soft-tissue infections can be defined as infections of any of the layers within the soft tissuecompartment that are associated with necrotising changes. NSTI is an uncommon but life-threatening. Toresolve this, some authors have developed different diagnostic adjuncts such as finger tests, skin biopsies,bedside ultrasounds and laboratory parameters in distinguishing NSTI from other soft-tissue infections(LRINEC laboratory risk indicator for necrotizing fasciitis score). Material and Method : An observationalstudy was conducted in 50 patients (clinically diagnosed necrotising soft tissue infection). clinicalobservations supported by relevant investigations were documented on the attached proforma and the data soobtained was statistically analysed. Observation and result : The results suggested that maximum numberof affected individuals are males, middle aged individuals. Majority of patients had normal pulse with meanbody temperature of 37.3°C, normal blood pressure,INR, normal serum level of sodium, potassium andbilirubin. High level of RBS (more than 200mg/dl). Tenderness was the most commonly elicited clinicalsign of NSTI, crepitus was noted in only 20% patients. Maximum number of patients were found to beinfected by streptococcus pyogenes (42%). The mean level was -hemoglobin -10.2+2.3 g/dl, WBC -13,340+ 6116 /mm3, serum creatinine value of s 1.6mg/l. High discrepancy noted in value of CRP. High prevalenceof NSTI involving the extremities ranging from 64.39% to 93.The mean value of LRINEC score is 6±2.9236 % of patients having 6. Conclusion : It can be concluded thatthe local clinical findings are of paramount importance rather than clinical features of systemic toxicity suchas fever and tachycardia.
Keywords: Clinical Profile, Evaluation, LRINEC score